Development and testing of a nurse-led program to improve health privacy practices of nurses - Chin, Roren Marie M. (Manila College of Nursing University of the Philippines Manila, 2024)
The growing complexities in healthcare have increased the risk to patients’ health data privacy violations and an overall unsafe delivery of basic health services. As coordinators of care, nurses spend the most time with patients managing their health data and are in a critical position to protect privacy or heighten the risk to privacy breaches. Despite the great need, there is a dearth of literature on effective initiatives to enhance the health privacy practices of nurses. Hence, developing interventions to improve health privacy practices of nurses and testing its efficacy in the real-world setting is a significant gap that needs to be filled to protect the healthcare consumers' rights to privacy.

The study proposes a model of health practices of nurses working in clinical settings through testing a nurse-led intervention to improve the health privacy practices of nurses. The 2-phase, 3-month nurse-led intervention (Embedding privacy and Confidentiality in Nursing Practice Training Program [EPiC-NP]) is informed by a systematic review and expert recommendations and guided by the Six Steps in Quality Intervention Development (6SQuID) model. The study used a quasi-experimental design with a matched active control group to examine the effect of the proposed nurse-led intervention on health privacy knowledge, skills, and attitudes. Process evaluation was also employed to explore the content surrounding the intervention implementation.

Twenty-five (25) nurses were assigned to receive EPiC-NP, while 22 received the usual Data Privacy Act training as active control belonging to two (2) comparable intensive care units. The results showed that health privacy skills are a significant predictor of attitudes, and vice-versa. However, the EPiC-NP program did not significantly improve health privacy skills, attitudes, and knowledge. Profile plot trends illustrated the potential greater influence of the EPiC-NP program on the health privacy skills and attitudes of nurses. The process evaluation revealed intrapersonal, interpersonal, and institutional challenges experienced by nurses such as competing priorities, non-preference to online mode of learning, and technical problems. This also identified opportunities; it specifically emphasized the intervention's main strengths, which include effectively managing challenging situations by incorporating informative lectures and ensuring that the activities are applicable to nurses’ real-world practice.

The findings indicate that EPiC-NP is an acceptable and appropriate intervention and has the potential to enhance health privacy practices of nurses. A model of health privacy practices of nurses was also proposed to understand the role of intrapersonal, interpersonal, and institutional systems to target significant improvements in privacy protection. Recommendations for future research, policy implementation, and practice changes are also presented. Further research is encouraged to examine the efficacy of the EPiC-NP program with a larger sample, different nursing care setting, and more favorable safety climate and work environment.
Dissertation (Doctor of Philosophy in Nursing) -- University of the Philippines Manila, July 2024.
Bibliography: 223-231 leaves.
Keywords: Nursing -- Practice; Health -- Privacy practices